Influence of Feeding Different Forms of Cottonseed on Nutrient Digestibility, Nitrogen Balance and Reproductive Performance of Lactating Cows - Ganie, Ajaz Ahmad; Mir, I.A.; A., Fayaz; Sheikh, Fayaz A.; Sehgal, J.P. (Indian Journal of Animal Nutrition, 2018)
Eighteen early lactating cows were randomly divided into 3 groups of 6 animals each to determine the effects of inclusion of crushed whole cottonseed or expeller processed cottonseed cake on nutrient utilization and reproductive performance of lactating cows. In control group (C), the cows were fed with wheat straw, chaffed oats fodder and concentrate mixture while in groups T1 and T2, the animals were fed the same ration as in control group but 50% of groundnut cake in concentrate mixture was replaced with crushed whole cottonseed (T1) or expeller processed cottonseed cake (T2). The DM OM, CP, NDF and ADF intake was similar in different groups. However, the intake (kg/d) of CF and EE was higher (P